The Russian Federation’s Crime in The Bombing of Mariupol Theatre - Juan Davis Elhanan; Ariawan Gunadi (Fakultas Hukum Universitas Tarumanagara, 2022)
This journal discusses the crimes that have been committed by The Russian Federation in their conflict with Ukraine, specifically the bombing of the Mariupol theatre during the siege of Mariupol and the violations of human, especially civilian rights in the process. The Mariupol Theatre was a national heritage preserving the culture and history of Ukraine and was utilized as a shelter for civilians from shelling, airstrikes, and bombings during the invasion. It was sheltering a large number of Civilians when the Russian Armed Forces decided to deliberately bomb the site, killing countless of innocent civilians sheltering from the attacks. Ukraine accused the Russian forces for deliberate attacks on civilians in the bombing of the theatre, but Russia denied all the claims in front of the international community. Russia initially claimed that the theatre was used by the Ukrainian military as a base and shelter, so they bombed the theatre purely under military necessity. The Russian claims have since been refuted by multiple independent investigations looking into the case. This attack and acts of aggression can be constituted as a war crime by the Organization for Security and Co-operation in Europe and Amnesty International, and have several times breached the authority of The Geneva Conventions. Russia have yet answered and been charged to these war crimes and allegations since the culprit and main perpetrator, in this case president of Russia Vladimir Putin, has to be brought forth in front of The International Criminal Court (ICC).